2015
DOI: 10.1371/journal.pone.0132450
|View full text |Cite
|
Sign up to set email alerts
|

Construction, De-Novo Assembly and Analysis of Transcriptome for Identification of Reproduction-Related Genes and Pathways from Rohu, Labeo rohita (Hamilton)

Abstract: Rohu is a leading candidate species for freshwater aquaculture in South-East Asia. Unlike common carp the monsoon breeding habit of rohu restricts its seed production beyond season indicating strong genetic control over spawning. Genetic information is limited in this regard. The problem is exacerbated by the lack of genomic-resources. We identified 182 reproduction-related genes previously by Sanger-sequencing which were less to address the issue of seasonal spawning behaviour of this important carp. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…In this network, we determined that the TCONS_00429684/TCONS_00309450-ssc-miR-1249-GRIK4 interaction axis was involved in the regulatory network. Concerning mRNAs, function enrichment analyses showed that GRIK4 has been involved in a reproduction-relevant pathway, such as neuroactive ligand-receptor interactions, which play important roles in reproduction processes [46]. In the present study, high levels of GRIK4 expression was noticed in the LH group compared with the LL group.…”
Section: Discussionsupporting
confidence: 49%
“…In this network, we determined that the TCONS_00429684/TCONS_00309450-ssc-miR-1249-GRIK4 interaction axis was involved in the regulatory network. Concerning mRNAs, function enrichment analyses showed that GRIK4 has been involved in a reproduction-relevant pathway, such as neuroactive ligand-receptor interactions, which play important roles in reproduction processes [46]. In the present study, high levels of GRIK4 expression was noticed in the LH group compared with the LL group.…”
Section: Discussionsupporting
confidence: 49%
“…In this network, we determined that the TCONS_00429684/TCONS_00309450-ssc-miR-1249-GRIK4 interaction axis was involved in the regulatory network. Concerning mRNAs, function enrichment analyses showed that GRIK4 has been involved in a reproduction-relevant pathway, such as neuroactive ligand-receptor interactions, which play important roles in reproduction processes [47]. In the present study, high levels of GRIK4 expression was noticed in the LH group compared with the LL group.…”
Section: Discussionsupporting
confidence: 49%
“…,; Sahu et al . ). Among the NGS techniques, Illumina sequencing and de novo assembly has gained popularity over Roche 454 and SOLID platforms in addressing the global mRNA expression levels in non‐model species (Wang et al .…”
Section: Introductionmentioning
confidence: 97%
“…The next-generation RNA sequencing and de novo assembly of the sequences have taken precedence over whole genome sequencing in obtaining functional information on non-model organisms (Firmino et al 2013;Schunter et al 2014). This is also the preferred method for identification of simple sequence repeats (SSRs) or microsatellites that assist in genetic diversity studies (Luikart et al 2003;Sahu et al 2015). Among the NGS techniques, Illumina sequencing and de novo assembly has gained popularity over Roche 454 and SOLID platforms in addressing the global mRNA expression levels in non-model species Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%